Influence of Non-metallic Inclusions on Corrosive Properties of Polar Steel - Li, Ming; Wu, Huajie; Sun, Yanhui (Frontiers in Materials, 2021)
Polar steel requires excellent toughness and corrosion resistance for breaking icy surfaces in low-temperature seawater environments. In this study, the effect of inclusions on the corrosion resistance of polar steel was examined. In the experiments conducted, the composition and morphology of the inclusions in steel were controlled using different deoxidation methods during steel refining. The morphology and composition of the corrosion-resistant active inclusions were analyzed using scanning electron microscopy and energy dispersive spectroscopy. The corrosion resistance of polar steel was determined by measuring the saturation current density of the anodic dissolution of steel in a corrosive medium via an electrochemical method. The corrosion resistance under simulated seawater was also investigated under laboratory conditions. It was found that as the ratio of Al/Mg approaches the stoichiometric composition of the spinel (2.3–2.5), the inclusions become less active; as the ratio increases further, the corrosion-resistant activity increases due to the formation of MgAl2O4⋅CaO complexes, leading to an increase in local stress around the inclusions. If steel is deoxidized with Zr–Ti, small Zr–Ti complex oxides form in the steel, providing nucleation particles for the precipitation of spheroidized and uniformly distributed MnS. Therefore, steel deoxidized with Zr–Ti has better seawater corrosion resistance than Al-deoxidized steel.